Efektifitas Jus Nanas terhadap Keputihan (Fluor albus) pada Wanita Usia Subur (WUS) - Sofia Mawaddah (Jurnal Kesehatan, 2019)
The mechanism of action of inhibition of pineapple extract against Staphylococcus aureus is a bromelain enzyme which is a proteolytic enzyme that plays a role in protein breakdown. The workings of the bromelain enzyme that inhibits the bacterium Staphylococcus aureus is to reduce the surface tension of the bacteria by hydrolyzing proteins and glycoproteins. This study also found that pineapple extract concentration of 70% is an effective concentration in inhibiting the growth of bacteria that cause vaginal discharge. The purpose of this study was to determine the effectiveness of pineapple juice against leucorrhoea (Fluor albus) in women of childbearing age (WUS) in the Pahandut Seberang district of Palangkaraya City. The research method used was the Quasy Experiment with the Pretest and Postest Nonequivalent Control Group design. The sample in this study amounted to 70 divided into 2 groups: 35 mothers were given pineapple juice and 35 mothers were given vaginal discharge. The sampling technique used is non-random with data analysis using the Man-Whitney test. Statistical test results with the Man-Whitney test showed that the p-value=0,000 (p<0,05) which showed that there was an influence of giving pineapple juice on vaginal discharge in women of childbearing age in the Pahandut Seberang Kelurahan of Palangka Raya.